Improving the Confidence of Middle School Students Given a Negative Label Through Group Counseling - Elsa Elsa; Alizamar Alizamar (Jurnal Neo Konseling, 2019)
Self-confidence is needed by students, so students are able to develop their competencies with confidence. Ideally, self-confidence of students must be in the high category. However, the reality is that there are still many students at school, especially students who are labeled negative have low self-confidence. Various studies have been conducted with regard to confidence with certain variables. This study focuses on testing the increase in self-confidence of students who are labeled negatively through group guidance. This research uses quantitative methods with the one group pretest-posttest design experimental approach. The research subjects were 10 students in Padang 33 Junior High School who were labeled negative. Data collection techniques using a questionnaire with a Likert scale model. This research was conducted in July-August 2019. Data collected was analyzed using the Wilcoxon Signed Rank Test formula with the help of Statistical Product and Service Solution (SPSS) Version 20. Based on the results of the study found there were differences in the increase in self-confidence of students who were labeled negative on when the pretest is in the medium category and the posttest is in the high category. Therefore BK teachers are advised to be able to develop group guidance services to help increase student confidence.